Embodiment of Early Psychosocial Adversity and Allostatic Load Using a Life Course Perspective: A Review - Barbosa Solís DDS, MSc, Cristina (Odovtos - International Journal of Dental Sciences, 2015)
The role of early life experiences on health is a major concern for research and public health interventions. Recent studies show that being exposed to chronic psychosocial stress during sensitive periods of development can have an impact on later health. It appears that children exposed to adverse conditions (economic, material and psychosocial) show a higher risk of adopting deleterious health behaviors (smoking, alcohol), heightened vulnerability to chronic diseases and mortality. Allostatic load (AL) is a measure of overall physiological wear-and-tear that can be the consequence of early life exposures. AL could allow for a better understanding of the potential biological pathways linking adverse exposures and later health. Here we review current evidence to discuss a biological embedding hypothesis, focusing on adverse psychosocial exposures during childhood and its effects on later AL, taking a life course perspective. Via a non-systematic review of recent literature, we examine whether adverse childhood experiences (ACE), causing chronic stress responses, may alter physiological functioning, as measured by AL. A better understanding of the biological mechanisms underlying psychosocial exposures could contribute to the development of more adapted public health interventions, both at a societal and individual level.